(untitled) (Publicaciones en Ciencias y Tecnología, 2017)
This review describes the work and the raison of the TEPUY Network, as an interdisciplinary group of experts dedicated to the research, development and implementation of Artificial Intelligence, Internet of Things (IoT) and Complex Systems technologies, in areas such as 4.0 industry and smart cities, among others. This paper shows the background, results and how it is organized. Finally, projects in development and future work are presented.